2016
DOI: 10.1075/slcs.176.06irw
|View full text |Cite
|
Sign up to set email alerts
|

The Rendaku Database

Abstract: Of those studies which have examined rendaku from a statistical angle, most have been small-scale, employing restricted corpora or micro-databases and often focused on specific conditions. The lack of a large-scale corpus was the impetus behind the creation of the Rendaku Database, available online for ongoing and future research. In this paper, both the initial and non-initial elements of approximately 28,000 compounds are subjected to a detailed analysis: by vocabulary stratum, length, part of speech, accent … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
15
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(15 citation statements)
references
References 115 publications
0
15
0
Order By: Relevance
“…I employ two complementary compound databases for investigating various phonological restrictions of Rendaku in this paper. The main database that I use, Irwin et al (2020), is a collection of all 35,328 Rendaku candidate compounds that are found in two major dictionaries, Kenkyūsha (Watanabe et al 2008) and Kōjien (Shinmura 2008). Here, Rendaku candidate compounds refer to the compounds whose W B begins with a voiceless obstruent and does not include a voiced obstruent.…”
Section: Corpus Studymentioning
confidence: 99%
See 2 more Smart Citations
“…I employ two complementary compound databases for investigating various phonological restrictions of Rendaku in this paper. The main database that I use, Irwin et al (2020), is a collection of all 35,328 Rendaku candidate compounds that are found in two major dictionaries, Kenkyūsha (Watanabe et al 2008) and Kōjien (Shinmura 2008). Here, Rendaku candidate compounds refer to the compounds whose W B begins with a voiceless obstruent and does not include a voiced obstruent.…”
Section: Corpus Studymentioning
confidence: 99%
“…As I am investigating phonological restrictions of Rendaku, I excluded items that could potentially be affected by other factors that have been reported to dampen Rendaku. Irwin et al (2020) not only includes noun-noun compounds but also those that are comprised of verbs or adjectives; I excluded compounds that are only comprised of verbs as these rarely undergo Rendaku (Okumura 1955;Vance 2008;Irwin 2012). Irwin et al (2020) includes compounds with elements from any of the Japanese lexical strata: Yamato (native), Sino-Japanese, or foreign.…”
Section: Corpus Studymentioning
confidence: 99%
See 1 more Smart Citation
“…8 Unfortunately, rendaku applies mainly to native items, and native items rarely contain non-geminate /p/, because Japanese lost this phoneme at some point in its history (Ueda 1898;Frellesvig 2010;Takayama 2015). In the rendaku database (Irwin 2016b;Irwin & Miyashita 2016), there is one monomorphemic native stem that contains /p/ or /pp/, suppa-i 'sour', which undergoes rendaku (e.g. ama-zuppa-i 'sweet and sour').…”
Section: Summary Of Arguments and Further Considerationsmentioning
confidence: 99%
“…To the best of our knowledge, the other aspects of our results have not been tested against the existing patterns of rendaku in the lexicon of contemporary Japanese. We can objectively address this question-whether the current results can be deduced from the patterns in the lexicon-once a comprehensive lexical database on rendaku is in place (see Irwin & Miyashita 2013 for an on-going attempt to build a lexical database on rendaku). Finally, our experiment examined the identity avoidance at the moraic level (CV units), because CV units are important phonological units in Japanese prosodic organization (Itô, 1989;Kubozono, 1989;Labrune, 2012), and also because found the effect of moraic identity avoidance in Japanese-(3a) and (3b) both violate consonantal identity avoidance, but only (3b) violates moraic identity avoidance.…”
Section: Remaining Questionsmentioning
confidence: 99%